Pulmonary metastasis of matrix-producing carcinoma mimicking small cell lung cancer. (2022) - Nakamura, Azusa; Suzuki, Mikito; Shimizu, Reiko; Shima, Toshiyuki; Harada, Masahiko; Hishima, Tsunekazu; Horio, Hirotoshi
Abstract: Matrix-producing carcinoma (MPC) of the breast is an extremely rare subtype of invasive breast cancer. MPC is characterized by the production of a cartilaginous or osseous matrix without spindle cells. It is an aggressive carcinoma, often presenting as triple-negative breast cancer. MPC frequently metastasizes to the lungs; however, it rarely reoccurs as a solitary pulmonary metastasis. We report a case of a 77-year-old non-smoking woman with a solitary pulmonary metastasis of MPC, which mimicked small cell lung cancer (SCLC). Initially, the pulmonary metastasis was misdiagnosed as SCLC based on its morphological and immunochemical features, including focal positivity for CD56 and thyroid transcription factor-1. Although the portion of the chondromyxoid matrix of the primary site was not small, that of the metastatic site was small. A focal cartilaginous matrix deposition of pulmonary metastasis from MPC could make it difficult to differentiate from SCLC. We should acknowledge that the portion of chondromyxoid matrix may differ between primary and distant metastatic sites in MPC.